COGNITIVE RESPONSE OF FOURTH SEMESTER ENGLISH EDUCATION STUDENTS CLASS D ON THE NARRATIVE OF DOLPHIN INTELLIGENCE ON SOCIAL MEDIA - Muziatun Muziatun; Nurul Ainun A.Dj. Panua; Fadlan Kaharu; Novira Nento; Indri Hamida Ntuna; Gusti Ngurah Ariawan (LPPM Universitas Pahlawan Tuanku Tambusai, 2026)
Social media has become an important source of information for students, influencing how they understand and interpret various topics. One type of content that frequently attracts attention is information about intelligent animals, particularly dolphins. This study aimed to explore the cognitive responses of fourth-semester students of English Education Class D toward content about dolphin intelligence on social media. This study employed a descriptive qualitative method. The participants consisted of nine fourth-semester student of English Education Class D. Data were collected through semi-structured interviews after watched social media content about dolphin intelligen. Data were collected after participants watched dolphin-related content on social media platforms such as TikTok and YouTube. The findings showed that students demonstrated various cognitive responses, including understanding, interpreting, evaluating, and connecting the information with their prior knowledge. Most participants perceived dolphins as intelligent animals based on the information and visual evidence presented in the content. The narratives and visuals shared through social media influenced how students constructed their understanding of animal intelligence and formed their opinions about dolphins. The study concludes that social media content plays a significant role in shaping students’ cognitive responses and influencing the way they process information.